2021
DOI: 10.1093/abbs/gmab124
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2, negatively regulated by miR-20b-5p, contributes to 5-fluorouracil resistance of colorectal cancer cells via the JNK/ERK signaling pathway

Abstract: 5-Fluorouracil (5-FU) resistance has been long considered as an obstacle to the efficacy of chemotherapy in colorectal cancer (CRC). In this study, we demonstrated the role of miR-20b-5p-regulated syndecan-2 (SDC2) in 5-FU resistance of CRC cells. 5-FU-resistant SW480 CRC cells were established by treatment of SW480 cells with stepwise increase of 5-FU concentration. The results showed that SDC2 was expressed significantly higher in SW480/5-FU cells than in SW480/WT cells as revealed by quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…MiR-20b has an essential role in chemotherapy resistance. It has been demonstrated that the activation of Syndecan-2, a transmembrane receptor, is positively correlated with chemotherapy resistance [ 75 ]. Mechanistically, miR-20b diminishes the resistance of cancer cells to chemotherapy by targeting Syndecan-2 [ 75 ].…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-20b has an essential role in chemotherapy resistance. It has been demonstrated that the activation of Syndecan-2, a transmembrane receptor, is positively correlated with chemotherapy resistance [ 75 ]. Mechanistically, miR-20b diminishes the resistance of cancer cells to chemotherapy by targeting Syndecan-2 [ 75 ].…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%
“…It has been demonstrated that the activation of Syndecan-2, a transmembrane receptor, is positively correlated with chemotherapy resistance [ 75 ]. Mechanistically, miR-20b diminishes the resistance of cancer cells to chemotherapy by targeting Syndecan-2 [ 75 ]. Its capability to regulate the sensitivity of cancer cells to chemotherapy drugs through hypoxia signaling pathways has profoundly been displayed.…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%